Secretory granule neuroendocrine protein 1 (SGNE1) genetic variation and glucose intolerance in severe childhood and adult obesity - Charpentier Guillaume; Tichet Jean; Jouret Béatrice; Veslot Jacques; Proença Christine; Heude Barbara; Lecoeur Cécile; Vatin Vincent; Bouatia-Naji Nabila; Marre Michel; Balkau Beverley; Froguel Philippe; et al. (BMC, 2007)
Abstract Background 7B2 is a regulator/activator of the prohormone convertase 2 which is involved in the processing of numerous neuropeptides, including insulin, glucagon and pro-opiomelanocortin. We have previously described a suggestive genetic linkage peak with childhood obesity on chr15q12-q14, where the 7B2 encoding gene, SGNE1 is located. The aim of this study is to analyze associations of SGNE1 genetic variation with obesity and metabolism related quantitative traits. Methods We screened SGNE1 for genetic variants in obese children and genotyped 12 frequent single nucleotide polymorphisms (SNPs). Case control analyses were performed in 1,229 obese (534 children and 695 adults), 1,535 individuals with type 2 diabetes and 1,363 controls, all French Caucasians. We also studied 4,922 participants from the D.E.S.I.R prospective population-based cohort. Results We did not find any association between SGNE1 SNPs and childhood or adult obesity. However, the 5' region SNP -1,701A>G associated with higher area under glucose curve after oral glucose tolerance test (p = 0.0005), higher HOMA-IR (p = 0.005) and lower insulinogenic index (p = 0.0003) in obese children. Similar trends were found in obese adults. SNP -1,701A>G did not associate with risk of T2D but tends to associate with incidence of type 2 diabetes (HR = 0.75 95%CI [0.55-1.01]; p = 0.06) in the prospective cohort. Conclusion SGNE1 genetic variation does not contribute to obesity and common forms of T2D but may worsen glucose intolerance and insulin resistance, especially in the background of severe and early onset obesity. Further molecular studies are required to understand the molecular bases involved in this process.